Characterisation of a label‐free biosensor based on long period grating. Issue 5 (2nd November 2012) - Chiavaioli, Francesco; Trono, Cosimo; Giannetti, Ambra; Brenci, Massimo; Baldini, Francesco
Abstract Optical fibre gratings, especially long period gratings, have been recently proposed as optical devices for biochemical sensing. A biochemical interaction along the grating portion induces a refractive index change and hence a change in the fiber transmission spectrum. This provides an alternative methodology with respect to other label‐free optical approaches, such as surface plasmon resonance, interferometric configurations and optical resonators. The fibre biofunctionalization has been carried out by means of a novel chemistry using Eudragit L100 copolymer as opposed to the commonly used silanization procedure. Antigen‐antibody interaction has been analysed by means of an IgG/anti‐IgG bioassay. The biosensor was fully characterised, monitoring the kinetics during the antibody immobilization and the antigen interaction and achieving the calibration curve of the assay. A comparison of the biosensor performance was made by using two different long period gratings with distinct periods. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)